The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.1515/hf-2017-0051
|View full text |Cite
|
Sign up to set email alerts
|

The minimum moisture threshold for wood decay by basidiomycetes revisited. A review and modified pile experiments with Norway spruce and European beech decayed by Coniophora puteana and Trametes versicolor

Abstract: Abstract:To know the minimum moisture threshold (MMThr) in wood allowing for the initiation of the fungal decay by basidiomycetes is relevant both from a theoretical and a practical point of view. The present work summarizes the knowledge about MMThr and presents experimental data obtained by improved laboratory decay tests on Picea abies (Norway spruce) and Fagus sylvatica (European beech) with the fungi Coniophora puteana and Trametes versicolor under different exposure scenarios well suited for simulation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 16 publications
1
17
0
Order By: Relevance
“…After a total exposure time of one year, no signs of wood decay were observed for all samples. This is generally in line with experiments in literature which do not include a liquid water source and in which the MC is below FSP [12,13]. This might indicate that onset of decay cannot happen if there is no liquid water source available and if the moisture content of the wood is below FSP.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…After a total exposure time of one year, no signs of wood decay were observed for all samples. This is generally in line with experiments in literature which do not include a liquid water source and in which the MC is below FSP [12,13]. This might indicate that onset of decay cannot happen if there is no liquid water source available and if the moisture content of the wood is below FSP.…”
Section: Discussionsupporting
confidence: 91%
“…Various laboratory experiments are reported in literature to define the minimal moisture threshold for fungal decay (a.o. [9][10][11][12][13]). In these tests, it is specifically investigated whether fungal decay is possible below 'fibre saturation point'.…”
Section: Introductionmentioning
confidence: 99%
“…Different fungi have different moisture requirements for successful infestation of wood (Meyer and Brischke, 2015 ; Brischke et al, 2017 ). Yet, our data suggest that the extractives do not play a key role in the moisture regulation of our larch specimen, as the MC was not different enough between the extracted and native samples to explain the differences we found in degradation.…”
Section: Discussionmentioning
confidence: 99%
“…One role of the more hydrophobic extractives is possibly to repel water, as the amount of moisture in the wood is critical for the fungus' successful establishment (Meyer and Brischke, 2015 ; Brischke et al, 2017 ). For instance, it has been suggested that a certain cell wall moisture content is needed to form pathways within the cell walls to allow diffusion of the fungal low molecular weight substances (Zelinka et al, 2015 ; Hunt et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several previous studies have addressed the relationship between moisture content and fungal activity (studies cited in (15,16), some of which have pointed to a risk of fungal attack even below the fibre saturation point, reaching the limit value of 16.3% in Picea abies (15). The risk of moisture leading to wood decay, however, is commonly considered to be above a moisture content of 20 to 30% (16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%